Fentanyl and Sufentanil in Labor Analgesia and Lactational Mastitis Risk: Evidence from a Retrospective Cohort Combined with Network Pharmacology - Qing Song; Mengjuan Li; Qi Wang; Qing Zhao; Jiayan Luo; Wei-Yi Wu; Shih-Pin Lee (Breastfeeding Medicine, 2026)
Background: Lactational mastitis (LM) is a common postpartum inflammatory disorder. Fentanyl and sufentanil are widely used for labor analgesia; however, their association with postpartum LM and the underlying molecular mechanisms remain unclear. Methods: A single-center retrospective cohort study including 201 women was conducted to evaluate the association between sufentanil-based neuraxial labor analgesia and the occurrence of postpartum LM using logistic regression. In parallel, network pharmacology, protein–protein interaction analysis, Gene Ontology/Kyoto Encyclopedia of Genes and Genomes enrichment, and molecular docking were performed to explore fentanyl- and sufentanil-related molecular targets and potential mechanisms. Results: Women receiving sufentanil-based neuraxial labor analgesia had a higher incidence of LM than women without labor analgesia, and logistic regression showed increased odds of LM in the exposed group (odds ratio = 8.758). Network pharmacology identified 20 shared targets between the drugs and LM, with core nodes including tumor necrosis factor (TNF), IL6, epidermal growth factor receptor (EGFR), ESR1, and NR3C1, which were mainly enriched in inflammation- and stress-related pathways such as NF-κB, mitogen-activated protein kinase (MAPK) and HIF-1. Molecular docking indicated that both opioids could form stable interactions with multiple targets involved in inflammation, endocrine regulation, and cell survival. Discussion: The clinical findings suggest a potential association between sufentanil-based neuraxial labor analgesia and postpartum LM, while the network pharmacology and molecular docking analyses provide hypothesis-generating evidence for opioid-related inflammatory, immune, endocrine, and tissue-repair pathways. Prospective studies are needed to validate these findings and clarify causality.